Pediatric rehabilitation principles and practice - Houtrow, Amy; McMahon, Mary A.; Murphy, Kevin P. 1956- (New York, NY Springer Publishing Company, LLC, 2021)
This revised and greatly expanded sixth edition of Pediatric Rehabilitation continues to set the standard of care for clinicians and remains the premier reference dedicated to education and training in the field of pediatric rehabilitation medicine. Under the direction of a new editorial team, this text brings together renowned specialists from all sectors of the pediatric rehabilitation community to provide the most current and comprehensive information with evidence-based discussions throughout. The sixth edition encompasses substantial updates from beginning to end and addresses emerging topics in the field with eight entirely new chapters devoted to brachial plexus palsy, oncology, robotics, genetics, spasticity management, rheumatology, burns, and advocacy. Major revisions to chapters on spinal cord injuries, acquired brain injury, cerebral palsy, neuromuscular diagnoses, and medical care of children reflect recent advances and expand coverage to include pediatric stroke, anoxic brain injury, bone health, pain management, and more. Chapter pearls, detailed summary tables, and over 250 figures emphasize major takeaways from the text for readers. With contributors chosen both for their academic and clinical expertise, chapters offer a real hands-on perspective and reference the most up to date literature available"--
History and Physical Examination / Dennis J. Matthews and Maureen R. Nelson -- Medical Care of Children with Disabilities / Susan D. Apkon, Amy Kanallakan, and C. Rashaan Ford -- Disorders of Communication and Oral Motor Function / Rita Ayyangar, Lynn Driver, and Marie VanTubbergen -- Psychological Assessment / Melissa Sutcliffe and Krestin Radonovich -- Gait Analysis / Aloysia L. Schwabe and James J. Carollo -- Hypertonia / Mark E. Gormley Jr. and Supreet Deshpande -- Guidance Techniques for Chemodenervation / Katharine E. Alter and Stephen A. Nichols -- Electrodiagnosis / Maureen R. Nelson, Nicholas Fleming, and Nicole Marcantuono -- Chronic Pain / Gadi Revivo, Diane K. Amstutz, and Matthew Haas -- Advocacy / Kerstin M.L. Sobus, Michael A. Alexander, Maria Fragala-Pinkham, and Jerie Beth Karkos -- Orthotics and Assistive Devices / Marcie Ward, Candice Johnson, Jennifer Klein, Janey McGeary Farber, William Nolin, and Michael J. Peterson -- Robotics / Mackenzie Brown, Justin Burton, Olga Morozova, and Sarah H. Evans -- Adaptive Sports and Recreation / Michelle A. Miller and Jill Meilahn -- Sport-Specific Musculoskeletal Injuries / Aaron M. Karlin and Nicholas P. Goyeneche -- Mild Traumatic Brain Injury / Nicole Marcantuono and Mary A. McMahon -- Acquired Brain Injury / Stacy Suskauer, Brad Kurowski, Beth Slomine, Nathan Evanson, and Nancy Yeh -- Cerebral Palsy / Jilda Vargus-Adams, Andrew Collins, and Andrea Paulson -- Demyelinating Conditions, Myelitis and Encephalitides / Amy J. Houtrow -- Musculoskeletal Conditions / Kevin P. Murphy, Elizabeth Moberg-Wolff, Mary E. Dubon, and Elaine L. Pico -- Limb Deficiencies / Phoebe Scott-Wyard, Vivian Yip, and David B. Rotter -- Rheumatologic Conditions / Colleen A. Wunderlich and Elaine L. Pico -- Genetic Conditions / Kelly L. D. Pham and Angela Sun -- Neuromuscular Conditions / Robert J. Rinaldi, Andrew Skalsky, and Kelli Chaviano -- Birth Brachial Plexus Palsy / Maureen R. Nelson -- Spinal Cord Injuries / Joseph E. Hornyak and Cory W. Wernimont -- Spina Bifida / Drew Davis and Erin Swanson-Kimani -- Burns / Sherilyn Whateley Driscoll and Karen Kowalske -- Cancer / David W. Pruitt, Ashlee K. Bolger, and Priya D. Bolikal -- Transition and Aging / Margaret A. Turk, Lynne Romeiser Logan, and Karl Klamar.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Disabled Children -- rehabilitation